Cardiac 18F‐Dopamine PET Distinguishes PD with Orthostatic Hypotension from Parkinsonian MSA. Issue 4 (23rd March 2021) - Lenka, Abhishek; Lamotte, Guillaume; Goldstein, David S.
ABSTRACT: Background: Parkinson's disease with orthostatic hypotension (PD + OH) can be difficult to distinguish clinically from the parkinsonian form of multiple system atrophy (MSA‐P). Previous studies examined cardiac sympathetic neuroimaging to differentiate PD from MSA but without focusing specifically on PD + OH versus MSA‐P, which often is the relevant differential diagnostic issue. Objective: To investigate the utility of cardiac sympathetic neuroimaging by 18 F‐dopamine positron emission tomographic (PET) scanning for separating PD + OH from MSA‐P. Methods: Cardiac 18 F‐dopamine PET data were analyzed from 50 PD + OH and 68 MSA‐P patients evaluated at the NIH Clinical Center from 1990 to 2020. Noradrenergic deficiency was defined by interventricular septal 18 F‐dopamine‐derived radioactivity <6000 nCi‐kg/cc‐mCi in the 5′ frame with mid‐point 8′ after initiation of 3′ tracer injection. Results: 18 F‐Dopamine PET separated the PD + OH from the MSA‐P group with a sensitivity of 92% and specificity of 96%. Conclusion: Cardiac 18 F‐dopamine PET scanning efficiently distinguishes PD + OH from MSA‐P.